Applying Data Science to Justice Systems: The North Carolina Statewide Warrant Repository (NCAWARE), 2014-2019 - Taniguchi, Travis ([Verlag nicht ermittelbar], 2022)
This study uses the data from the unified, statewide warrant repository NCAWARE (NC Arrest Warrant Repository) to evaluate a proposed system for processing and serving arrest warrants. The NCAWARE system is maintained by the North Carolina Administrative Office of the Courts (NCAOC). The study takes place within the Greensboro, NC police department where two of the four police districts utilized the system. This study is the result of the unorganized system for processing and serving warrants and the significant backlog of cases with outstanding warrants that exists across the country. One of the purposes of this study was to create a systematic approach for law enforcement agencies to prioritize the execution of warrants.